Dissecting the Initial One-Week Narratives of Al Jazeera and BBC Media on Covering Israel-Palestine Tension After 7 October 2023 - Mochamad Alvin Dwiana Qobulsyah; Lily Liani; Paramita Amaranggana; Kennard Mikael (ULTIMA Comm, 2023)
Israel's military aggression in the Gaza Strip following Hamas's surprise attack on October 7th, 2023, continued to escalate until the end of the year, which became one of the deadliest military operations in the last three decades, with a total death toll of more than 10 thousand people. The coverage of the escalated tensions in Israel-Palestine has also become a hot issue to cover by various international media outlets. This article delved into the news narrative of the British Broadcasting Corporation (BBC) and Al Jazeera, examining their agenda-setting, language selection, and framing of events. The choice of BBC and Al Jazeera as the subjects of this research is to compare the representation of Western and non-Western media. Through the utilization of comparative methods and text analysis facilitated by Voyant tools, this study revealed that background differences between the observed media impact the news content disparities for international audiences in accordance with each interest.